Simple noun-head modification patterns in English and Binukid a descriptive-contrastive analysis - Fornilos, Deogracias Valmores 1939- (s.n.], 1974)
As a descriptive-contrastive analysis of noun-head modification structures in English and Binukid, this study focuses on simple noun-head patterns where a single noun is used as head and a single word in the form of another noun, verb, adjective, adverb, function word or a prepositional phrase is used as a modifier. This is an attempt to lay the foundation for the preparation of teaching and testing materials for structures of modification among Bukidnon learners of English.